Current conservative treatment of uterine fibroids. Ulipristal acetate and liver damage: contrived tragedy? - A L Tikhomirov (IP Berlin A.V., 2018)
Uterine fibroids are the most common pelvic tumor formation in women and the most common indication for hysterectomy. The effectiveness of long-term intermittent use of ulipristal acetate (UA) in patients with uterine myoma has been proven earlier. In May 2018, the ability of UA to cause a drug-induced liver injury (drug-induced liver injury, DILI) was disproved, and the European Commission approved a positive decision. According to the conclusion Expertise of the Pharmacovigilance Risk Assessment Committee (Pharmacovigilance Risk Assessment Committee - PRAC) the benefit/risk ratio remains favorable. Published recommendations are aimed at reducing the risk of liver damage. UA remains the 1st line of treatment for most myomas.